Privolitev za patentiranje človeškega biološkega materiala - Pohar, Klemen (Podjetje in delo, 2016)
In the competitive field of biotechnology, where research is associated with high costs, patenting is nowadays a common practice. When biotechnological inventions are based on research of human biological material, the will of the donor regarding the activities associated with this material has to be respected. An individual can have different reasons to oppose particular activities associated with the material taken from his body, and the law requires compliance with his will. When the will of the donor is not respected, the law on personality rights offers certain remedies. It does not, however, regulate the situation when an intervention into a person' s body is the basis of a new intellectual property right. This situation is subject to research in patent law. The author researches the question whether consent for patenting is or should be a condition for patentability of an invention developed on the basis of research of human biological material.
Keywords: biotehnologija; človekove pravice; človeški genom; patentiranje